Gallium oxide material loaded with iridium cluster as well as preparation method and application of gallium oxide material
By loading iridium clusters on the surface of gallium oxide to form a Ga-O-Ir interface, the problem of poor stability of iridium oxide catalysts in PEMWE is solved, efficient long-term stable operation and electrochemical performance are achieved, and the use and cost of iridium are reduced. .
Patent Information
- Application Number
- CN202411392654.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The iridium oxide catalyst used in the existing proton exchange membrane water electrolytic cell (PEMWE) has problems with high cost and poor stability in a strong acid oxidation environment, resulting in slow kinetics and uncompetitiveness in the oxygen evolution reaction.
Using gallium oxide material with iridium clusters, prepared by a one-step hydrothermal reaction, the mass percentage of iridium content is ≤50%, and the iridium cluster is loaded on the surface of the gallium oxide to form a Ga-O-Ir interface to improve electrocatalytic activity and stability.
It significantly reduces the energy barrier of the oxygen evolution reaction, improves the electrochemical performance and cycle stability, and enables the catalyst to operate efficiently and stably for more than 1,000 hours under PEMWE conditions, far exceeding the performance of commercial catalysts.
Smart Images

Figure CN119194505A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to a gallium oxide material loaded with iridium clusters, a preparation method and an application thereof. Background Art
[0002] Proton exchange membrane water electrolyzer (PEMWE) has the advantages of high operating current density and H2 purity, low resistance loss, etc., making it the preferred technology for high-efficiency and small-footprint electrolyzers. However, the working conditions of PEMWE with strong acidity and oxidizing environment pose substantial challenges to the activity and stability of catalysts. These challenges are related to the slow kinetics of oxygen evolution reaction (OER) and the dependence on rare key catalysts. For example, iridium oxide (IrO2), an anode catalyst that has been popular so far due to its stability. On the one hand, the mass fraction of Ir in the current commercial supported iridium oxide catalyst is more than 75%, and Ir is one of the rarest metals on earth and has a high cost. On the other hand, the electrochemical performance of IrO2 cannot operate efficiently and stably for a long time under the working conditions of PEMWE, making PEMWE relying on iridium oxide catalysts not competitive in the market. For this reason, it is urgent to develop electrocatalysts with intrinsic activity, acid stability and low iridium to improve the competitiveness of PEMWE devices. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a gallium oxide material loaded with iridium clusters, and a preparation method and application thereof. The gallium oxide material loaded with iridium clusters provided by the present invention has a low Ir content (≤50wt%) and excellent electrochemical properties. Under PEMWE conditions, the gallium oxide material loaded with Ir clusters as a catalyst has both enhanced electrocatalytic activity and good long-term stability.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The present invention provides a gallium oxide material loaded with iridium clusters, comprising flaky gallium oxide and iridium clusters loaded on the surface of the gallium oxide:
[0006] The mass percentage of iridium in the gallium oxide material loaded with iridium clusters is ≤50%.
[0007] Preferably, the gallium oxide has a crystal form of ε-Ga2O3, a lattice structure of cubic structure, and a space group of Fd-3m (227).
[0008] The present invention provides a method for preparing the gallium oxide material loaded with iridium clusters as described in the above technical solution, comprising the following steps:
[0009] An Ir source, a gallium salt, an alkali source, an organic alcohol and water are mixed and subjected to a one-step hydrothermal reaction to obtain the gallium oxide material loaded with iridium clusters.
[0010] Preferably, the Ir source is iridium chloride.
[0011] Preferably, the gallium salt is gallium nitrate.
[0012] Preferably, the alkali source is potassium hydroxide.
[0013] Preferably, the organic alcohol is ethylene glycol.
[0014] Preferably, the temperature of the one-step hydrothermal reaction is 160-220° C., and the insulation time is 12-36 hours.
[0015] Preferably, the molar ratio of Ir in the Ir source to Ga in the gallium salt is (1-2):(1-8).
[0016] The present invention provides the use of the gallium oxide material loaded with iridium clusters described in the above technical solution or the gallium oxide material loaded with iridium clusters prepared by the preparation method described in the above technical solution as a catalyst in a proton exchange membrane water electrolyzer.
[0017] The present invention provides a gallium oxide material loaded with iridium clusters, comprising flaky gallium oxide and iridium clusters loaded on the surface of gallium oxide: the mass percentage of iridium in the gallium oxide material loaded with iridium clusters is ≤50%. The present invention adopts Ga2O3 as a substrate material and composites it with precious metal Ir, which can significantly reduce the mass percentage of precious metal Ir in the composite material (≤50%) and reduce the cost; in the electrocatalytic oxygen evolution reaction, after applying voltage, the gallium oxide material loaded with iridium clusters (Ir@Ga2O3) can generate an in-situ reconstructed Ga-O-Ir interface through bias-induced Ga leaching, and this Ga-O-Ir interface significantly reduces the energy barrier of the oxygen evolution reaction, greatly improves the reaction activity, and significantly improves its electrochemical performance (overpotential and cycle stability); the gallium oxide material loaded with iridium clusters can be used as a catalyst to operate stably and efficiently for more than 1000 hours under the working conditions of a proton exchange membrane water electrolyzer (PEMWE), far exceeding the performance and maximum operating time of commercial catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a spherical aberration transmission electron microscopy image of the gallium oxide material (Ir@Ga2O3 (1:1)) loaded with iridium clusters prepared in Example 1;
[0019] Figure 2 XRD pattern of the gallium oxide material (Ir@Ga2O3) loaded with iridium clusters prepared in Example 1;
[0020] Figure 3The OER polarization curves of the gallium oxide material loaded with iridium clusters and C-IrO2 prepared in Examples 1 to 5;
[0021] Figure 4 The OER polarization curves of the gallium oxide material loaded with iridium clusters (Ir@Ga2O3 (1:1)) prepared in Example 1 and Ga2O3 prepared in Comparative Example 1;
[0022] Figure 5 Polarization curves of the gallium oxide material loaded with iridium clusters (Ir@Ga2O3) and the commercial catalyst IrO2 (C-IrO2) prepared in Example 1 in PEMWE;
[0023] Figure 6 This is a chronopotentiometric curve of the gallium oxide material (Ir@Ga2O3) loaded with iridium clusters prepared in Example 1 in PEMWE. DETAILED DESCRIPTION
[0024] The present invention provides a gallium oxide material loaded with iridium clusters, comprising flaky gallium oxide and iridium clusters loaded on the surface of the gallium oxide:
[0025] The mass percentage of iridium in the gallium oxide material loaded with iridium clusters is ≤50%.
[0026] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0027] The gallium oxide material loaded with iridium clusters provided by the present invention comprises flaky gallium oxide.
[0028] As an embodiment, the gallium oxide has a crystal form of ε-Ga2O3, a lattice structure of cubic structure, and a space group of Fd-3m (227).
[0029] The gallium oxide material loaded with iridium clusters provided by the present invention comprises iridium clusters loaded on the surface of gallium oxide.
[0030] As an implementation manner, the mass percentage of iridium in the gallium oxide material loaded with iridium clusters is ≤50%.
[0031] The present invention also provides a method for preparing the gallium oxide material loaded with iridium clusters as described in the above technical solution, comprising the following steps:
[0032] An Ir source, a gallium salt, an alkali source, an organic alcohol and water are mixed and subjected to a one-step hydrothermal reaction to obtain the gallium oxide material loaded with iridium clusters.
[0033] As an embodiment, the Ir source is iridium chloride (H2IrCl6); the gallium salt is gallium nitrate (Ga(NO3)3); the alkali source is potassium hydroxide (KOH); and the organic alcohol is ethylene glycol (EG). The organic alcohol plays the role of a reducing agent and a template agent in the one-step hydrothermal reaction.
[0034] As an embodiment, the molar ratio of Ir in the Ir source and Ga in the gallium salt is (1-2):(1-8), and in specific embodiments it is 1:1, 2:1, 1:2, 1:4 or 1:8.
[0035] As an embodiment, the mass ratio of the gallium salt and the alkali source is (2-1):(1-2), and in a specific embodiment it is 2:1; the mass ratio of the gallium salt and the organic alcohol is (0.02-0.32):(10-15), and in a specific embodiment it is 0.04:11.3; the mass ratio of the gallium salt and water is (0.01-0.32):(10-30), and in a specific embodiment it is 0.04:25.
[0036] As an embodiment, the mixing is: firstly dispersing the Ir source and the gallium salt in water, then adding the alkali source for a first stirring, and finally adding the organic alcohol for a second stirring. As an embodiment, the first stirring rate is 3000-5000 rpm, and in a specific embodiment, it is 5000 rpm, and the time is 5 minutes; the second stirring rate is 3000-5000 rpm, and in a specific embodiment, it is 5000 rpm, and the time is 30 minutes.
[0037] As an embodiment, the temperature of the one-step hydrothermal reaction is 160-220°C, and the insulation time is 12-36 hours. In a specific embodiment, the temperature of the one-step hydrothermal reaction is 180°C, and the insulation time is 24 hours.
[0038] As an embodiment, the equipment used for the one-step hydrothermal reaction is a Teflon-lined stainless steel autoclave.
[0039] As an embodiment, after the one-step hydrothermal reaction, the method further comprises: cooling the product obtained from the one-step hydrothermal reaction to room temperature, washing and solid-liquid separation to obtain the gallium oxide material loaded with iridium clusters.
[0040] As an embodiment, the reagents used for washing are water and ethanol; the washing and solid-liquid separation are performed twice independently with each reagent; the solid-liquid separation is centrifugal separation; the rotation speed of the centrifugal separation is 11000 rpm and the time is 5 minutes.
[0041] The present invention also provides the use of the gallium oxide material loaded with iridium clusters described in the above technical solution or the gallium oxide material loaded with iridium clusters prepared by the preparation method described in the above technical solution as a catalyst in a proton exchange membrane water electrolyzer.
[0042] In the present invention, the use of the gallium oxide material loaded with iridium clusters as a catalyst in a proton exchange membrane water electrolyzer is preferably: the use of the gallium oxide material loaded with iridium clusters as a catalyst in a proton exchange membrane water electrolyzer to electrolyze water to produce hydrogen.
[0043] The present invention has no special limitation on the application of the gallium oxide material loaded with iridium clusters as a catalyst in a proton exchange membrane water electrolyzer, and any application method known in the art may be used.
[0044] In the electrocatalytic oxygen evolution reaction, after applying voltage, the gallium oxide material loaded with iridium clusters generates an in-situ reconstructed Ga-O-Ir interface through bias-induced Ga leaching. This Ga-O-Ir interface significantly reduces the energy barrier of the oxygen evolution reaction and greatly improves the reaction activity, making the gallium oxide material loaded with iridium clusters have excellent electrochemical properties.
[0045] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0046] Iridochloric acid (H2IrCl6), hydrated gallium nitrate (Ga(NO3)3·xH2O), ethylene glycol (EG) and potassium hydroxide (KOH) were purchased from Aladdin, analytical grade.
[0047] Example 1
[0048] First, 65 mg H2IrCl6 and 40 mg Ga(NO3)3·xH2O were dispersed in 25 mL water, the molar ratio of Ir in H2IrCl6 to Ga in Ga(NO3)3 was 1:1, 20 mg KOH was added to the resulting solution, and the mixture was stirred at 5000 rpm for 5 min. Then 10 mL ethylene glycol (1.13 g / mL) was added and stirred at 5000 rpm for 30 min. The resulting solution was transferred to a 50 mL Teflon-lined stainless steel autoclave and subjected to a one-step hydrothermal reaction at 180°C for 24 h. The product was cooled to room temperature and then washed with water and ethanol and centrifuged twice each at a speed of 11000 rpm for 5 min to obtain a gallium oxide material loaded with iridium clusters (Ir@Ga2O3(1:1)).
[0049] Example 2
[0050] The difference from Example 1 is that the molar ratio of Ir in H2IrCl6 and Ga in Ga(NO3)3·xH2O is 2:1.
[0051] Example 3
[0052] The difference from Example 1 is that the molar ratio of Ir in H2IrCl6 and Ga in Ga(NO3)3·xH2O is 1:2.
[0053] Example 4
[0054] The difference from Example 1 is that the molar ratio of Ir in H2IrCl6 and Ga in Ga(NO3)3·xH2O is 1:4.
[0055] Example 5
[0056] The difference from Example 1 is that the molar ratio of Ir in H2IrCl6 and Ga in Ga(NO3)3·xH2O is 1:8.
[0057] Comparative Example 1
[0058] 40 mg of Ga(NO3)3·xH2O was dispersed in 25 mL of water, 20 mg of KOH was added to the resulting solution, and the mixture was stirred at 5000 rpm for 5 min. Then 10 mL of ethylene glycol was added and the mixture was stirred at 5000 rpm for 30 min. The resulting solution was transferred to a 50 mL Teflon-lined stainless steel autoclave and subjected to a one-step hydrothermal reaction at 180°C for 24 h. The product was cooled to room temperature, washed with water and ethanol, and centrifuged twice each at a speed of 11000 rpm for 5 min to obtain Ga2O3.
[0059] Comparative Example 2
[0060] The commercial catalyst IrO2 was used as a comparative example.
[0061] Performance Testing
[0062] (1) Figure 1 The spherical aberration transmission electron microscopy images of the gallium oxide material (Ir@Ga2O3 (1:1)) loaded with iridium clusters prepared in Example 1, wherein a is the HAADF-STEM image of Ir@Ga2O3, b is the EDS mapping image of Ir, O and Ga in Ir@Ga2O3, c is the EDS mapping image of Ga in Ir@Ga2O3, d is the HAADF-STEM image of Ir@Ga2O3, e is the EDS mapping image of O in Ir@Ga2O3, and f is the EDS mapping image of Ir in Ir@Ga2O3. Figure 1It can be seen that in the gallium oxide material loaded with iridium clusters prepared by the present invention, Ir is mainly loaded on the carrier Ga2O3 in the form of clusters.
[0063] (2) Figure 2 This is the XRD pattern of the gallium oxide material (Ir@Ga2O3) loaded with iridium clusters prepared in Example 1. Figure 2 It can be seen that the XRD spectrum of the material prepared by the present invention mainly shows the peak spectrum of Ga2O3, the crystal form of gallium oxide is ε-Ga2O3, the lattice structure is a cubic structure, and the space group is Fd-3m (227).
[0064] (3) Figure 3 The OER polarization curves of the gallium oxide materials loaded with iridium clusters prepared in Examples 1 to 5 and the commercial catalyst IrO2 (C-IrO2) are shown in Figure 1. Figure 3 It can be seen that the OER performance of materials in different embodiments is different, among which Ir@Ga2O3 (1:1) prepared in Example 1 has the best OER performance, and it can be intuitively found that loading iridium clusters on gallium oxide materials has a significant improvement in OER performance.
[0065] (4) Figure 4 The OER polarization curves of the gallium oxide material loaded with iridium clusters (Ir@Ga2O3 (1:1)) prepared in Example 1 and Ga2O3 prepared in Comparative Example 1 are shown in FIG. Figure 4 It can be seen that Ga2O3 as a comparative example has almost no OER performance.
[0066] (5) Figure 5 Polarization curves of the gallium oxide material loaded with iridium clusters (Ir@Ga2O3) prepared in Example 1 and the commercial catalyst IrO2 (C-IrO2) in PEMWE. Figure 5 It can be seen that the Ir@Ga2O3 prepared by the present invention reaches 2A·cm under the working conditions of PEMWE (80℃). -2 The current density only needs 1.76V to reach 1A·cm -2 The current density only needs 1.63V, while the commercial catalyst IrO2 reaches 1A·cm -2 The current density needs to be 1.72 V. This shows that the performance of Ir@Ga2O3 prepared by the present invention in the proton exchange membrane water electrolyzer (PEMWE) is much higher than that of the commercial catalyst IrO2.
[0067] (6) Figure 6 This is a chronopotentiometric curve of the gallium oxide material (Ir@Ga2O3) loaded with iridium clusters prepared in Example 1 in PEMWE. Figure 6 It can be seen that the Ir@Ga2O3 prepared by the present invention can -2The degradation rate was only 11.5μV·h after stable operation for 1000h. -1 , while the commercial catalyst IrO2 can only run for less than 400 hours.
[0068] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A gallium oxide material loaded with iridium clusters, characterized in that: It includes flake gallium oxide and iridium clusters loaded on the surface of gallium oxide: The mass percentage of iridium in the gallium oxide material loaded with iridium clusters is ≤50%.
2. The gallium oxide material loaded with iridium clusters according to claim 1, characterized in that: The gallium oxide has a crystal form of ε-Ga2O3, a lattice structure of a cubic structure, and a space group of Fd-3m (227).
3. The method for preparing the gallium oxide material loaded with iridium clusters according to claim 1 or 2, characterized in that: The following steps are involved: An Ir source, a gallium salt, an alkali source, an organic alcohol and water are mixed and subjected to a one-step hydrothermal reaction to obtain the gallium oxide material loaded with iridium clusters.
4. The preparation method according to claim 3, characterized in that: The Ir source is iridium chloride.
5. The preparation method according to claim 3, characterized in that: The gallium salt is gallium nitrate.
6. The preparation method according to claim 3, characterized in that: The alkali source is potassium hydroxide.
7. The preparation method according to claim 3, characterized in that: The organic alcohol is ethylene glycol.
8. The preparation method according to claim 3, characterized in that: The temperature of the one-step hydrothermal reaction is 160-220° C., and the insulation time is 12-36 hours.
9. The preparation method according to claim 3, characterized in that: The molar ratio of Ir in the Ir source to Ga in the gallium salt is (1-2):(1-8).
10. Use of the gallium oxide material loaded with iridium clusters according to claim 1 or 2 or the gallium oxide material loaded with iridium clusters prepared by the preparation method according to any one of claims 3 to 9 as a catalyst in a proton exchange membrane water electrolyzer.
Citation Information
Patent Citations
Preparation method of high-activity iridium black catalyst
CN118595450A
Catalyst for catalytic reduction of nitrogen oxide
JP1994099068A
Cited By
Iridium-containing microcrystalline nanometer material and preparation method and application thereof
CN119640325A
Heterojunction catalyst with reconstructed surface as well as preparation method and application of heterojunction catalyst
CN121896674A
